The Phenomenon of Street Children in Criminology Studies (Study in Sambiroto, Semarang) - Tiyani, Vina Yunia; Triyana, Triyana; Kholisyatun N, Nisful; Wahyu A., Muhammad (Law Research Review Quarterly, 2019)
This research is motivated by the many irregularities that occur in urban areas such as the city of Semarang, for example the number of street children. This observation is done by jumping directly to the destination that is on Sambiroto Street, Semarang. There are various kinds of jobs for street children who sell newspapers, provide services to wipe the windshield when passing on the street and sell newspapers. The purpose of this observation is to find out what lies behind these children or adolescents as street children, and to study and analyze internal factors, such as within the scope of the family that makes them street children. To find out their work while on the streets, whether they work for themselves or told by others. The method used in this observation is using qualitative methods. Data collected by in-depth interviews, observation, and documentation. After the data has been collected, data analysis is carried out through the stages, namely data reduction, data presentation and conclusion drawing. The results of these observations show that the main factor that caused them to go to the streets is because of the family's economic limitations, so they voluntarily or with their own initiative to go into the streets by working on the streets. While on the road they often interact with other street children so that they eventually form a group or even a community. Interaction is woven for a specific purpose such as working together when plunging into the road.